Association of Insomnia, Lipid Profile, and Lipid-Lowering Medications: A Narrative Review - Fang Jia; Shun-Yi Shi; Si-Fan Fei; Min Zhou; Jian-Jun Li (Reviews in Cardiovascular Medicine)
Sleep is a fundamental phenomenon that helps maintain normal physiological processes. Conversely, sleep disorders, usually presented as insomnia, are a common public health problem that can lead to multiple pathophysiological changes in humans, including lipid metabolic abnormality. Interestingly, several previous studies have examined the potential relation of insomnia to metabolic syndrome and hyperlipidemia and found that insomnia was associated with elevated plasma cholesterol and triglyceride concentrations. This review summarizes evidence regarding the linkage between insomnia and lipid abnormalities. Moreover, the underlying physiologic mechanisms linking insomnia to lipid abnormalities are systemically discussed. Finally, issues with lipid-lowering drugs and the risk of insomnia are also presented. This knowledge can improve our understanding of the pathophysiological features of insomnia, which may help to prevent and treat insomnia-induced dyslipidemia clinically.